Government spending multipliers in natural resource-rich developing countries - Jean-Pascal Nguessa Nganou; Juste Somé; Guy Tchuente Nguembu (University of Kent, School of Economics, 2016)
This paper estimates the government spending multiplier for natural resource-rich low-income countries (LICs). Kraay (2014) identification strategy exploits the long lags between approval and eventual disbursement of loans to isolate a predetermined component of public spending associated with past loan approval decisions taken before the realization of contemporaneous shocks. However, he did not take into account the fact that natural resource extraction in a developing country can be linked to loan approvals and subsequent disbursements. Moreover, natural resources are an important source of public revenue for many LICs. For these reasons, we correct loans disbursement and control for natural resource rent to identify the government spending multiplier. Our estimates suggest that in the short run, the government spending multiplier is around 0.7 for natural resource-rich LICs. Government spending has a permanent impact on the real economic activity in resource-rich countries while having a transitory long-run impact in other countries.
Keywords: E62; O23; 330; Government spending multipliers; fiscal policy; natural resources